Racial/Ethnic Differences in Sleep Quality Among Older Adults with Osteoarthritis - Parmelee, Patricia A. (Sleep Health, 2017)
OBJECTIVE: To examine racial/ethnic differences in sleep quality and the pain-sleep association among older adults with osteoarthritis (OA) of the knee. DESIGN: Baseline interview followed by a 7-day microlongitudinal study using accelerometry and self-reports. SETTING: Participants were community residents in western Alabama and Long Island, NY. PARTICIPANTS: Ninety-six African Americans (AAs) and 128 non-Hispanic Whites (NHWs) with physician-diagnosed knee OA, recruited from a variety of clinical and community settings. Measurements: Self-reports yielded demographics, body mass index, physical health problems, and depressive symptoms. Sleep quality was measured over 3 to 7 nights using wrist-worn accelerometers; pain was self-reported daily over the same period. RESULTS: With demographics and health controlled, AAs displayed poorer sleep efficiency, greater time awake after sleep onset and sleep fragmentation, and marginally more awakenings during the night, but no differences in total sleep time (TST). AAs also showed greater night-to-night variability in number of awakenings and sleep fragmentation, and marginally greater variability in TST and sleep efficiency. Sleep quality was not associated with pain either the day before sleep nor the day after. Average daily pain interacted with race: whereas AAs displayed no effect of pain on sleep efficiency, NHWs exhibited better sleep efficiency at higher levels of average pain. CONCLUSIONS: These data corroborate previous studies documenting poorer sleep among AAs vs. NHWs. The findings of greater night-to-night variability in sleep among AAs, as well as a negative association of pain with sleep quality among NHWs, are unique. Further study is needed to elucidate these findings.